Modelling of Solar Power Generation Systems as a Source of Agricultural Irrigation Pumps - I Ketut Parti; Ni Wayan Rasmini; I Nyoman Mudiana; I Made Purbhawa (Postgraduate, University of Mataram, 2023)
New and renewable energy (EBT) is a green energy generator because its supply is abundant and will not run out all the time. Renewable energy is clean energy and does not produce pollution because it is not from fossil fuels such as natural gas, and it will not damage the environment on earth. One of the green energy generators is the Solar Power Plant (PLTS), one of the green energies developed by the Indonesian government to replace energy derived from fossil fuels. The government has set a National Energy Policy, targeting the contribution of NRE to the national energy mix by 2025 is 17% (Perpres No. 5/2006), amended by PP No.79/2014, 23% (2025, (31) % (2050) To be able to support this, it is hoped that a study and research will be carried out,